Robust converter-fed motor control based on active rejection of multiple disturbances. (February 2021) - Madonski, Rafal; Łakomy, Krzysztof; Stankovic, Momir; Shao, Sally; Yang, Jun; Li, Shihua
Abstract: In this work, an advanced motion controller is proposed for buck converter-fed DC motor systems. The design is based on an idea of active disturbance rejection control (ADRC) with its key component being a custom observer capable of reconstructing various types of disturbances (including complex, harmonic signals). A special formulation of the proposed design allows the control action to be expressed in a concise and practically appealing form reducing its implementation requirements. The obtained experimental results show increased performance of the introduced approach over conventionally used methods in tracking precision and disturbance rejection, while keeping similar level of energy consumption. A stability analysis using theory of singular perturbation further supports the validity of proposed control approach. Highlights: Robust controller is proposed for highly disturbed converter-fed motor system. Design is based on an idea of active disturbance rejection control (ADRC). Proposed solution can deal with complex disturbances, including harmonic signals Control action is expressed in a concise and practically appealing form. Proposed approach is validated with experiments and theoretical results.